Our preliminary experience with SPECT 99m Tc-HMPAO brain perfusion scans in diagnosis of dementia - Makazlieva, Tanja; Vaskova, Olivija; Crcareva, Biljana; Zdraveska-Kocova, Marina; Krsteska, Roza; Stoeva, Melita; Mukaetova-Ladinska, Elizabeta (My University, 2015)
ABSTRACT Introduction: Dementia is a clinical syndrome caused by a spectrum of different etiopathogenetic disorders, such as neurodegenerative, infective, expansive or other morphological processes in the brain tissue. Several studies indicate the possibility of differential diagnosis of dementia according to the findings of brain SPECT study. Aim: The objective of the paper is to present our preliminary experiences with SPECT 99mTc-HMPAO brain perfusion scintigraphy in the diagnosis of dementia. Materials and methods: 99mTc-HMPAO SPECT brain perfusion was performed on 9 patients selected after detailed neuropsychiatric investigations conducted by specialist psychiatrist. Obtained images were reconstructed with commercial software Mediso Brain SP128 and the qualitative and semiquantitative analysis of the data was carried out. Results: We found hypoperfusion defects in all evaluated patients, in most cases unilateral hypoperfusion in the left hemisphere, respectively in 56% of evaluated patients and in six out of nine, respectively in 67%, hypoperfusion of the left temporal lobe. Most common finding was parietal hypoperfusion, found in 8 patients (89%) and left mesial temporal lobe hypoperfusion, detected in 6 patients (67%). Conclusion: Findings of all the evaluated patients showed indisputable defects in perfusion which in correlation with clinical criteria give useful guidance in diagnosis of dementia. We concluded that it is necessary to continue with the prospective study of larger number of patients and with multidisciplinary approach in order to obtain relevant conclusions with statistical significance.
Keywords: 99mTc-HMPAO SPECT; dementia; brain perfusion